Analisis Harga Pokok Produksi Menggunakan Metode Full Costing dalam Penetapan Harga Jual (Studi Kasus Unit Usaha Camilan Kampungku) - Nur Aisyah Ramadhani; Muhammad Nasim Harahap (Peneliti.net, 2023)
The calculation of the cost of production is an important thing to note, because of the increasing competition between UMKM in producing quality products at quite competitive prices in the market. The researcher aims to find out how to calculate the cost of production to determine the selling price of products for UMKM Camilan Kampungku. The Full Costing method is a method of determining the cost of a product that takes into account all elements of production costs, which are both fixed and variable. The selling price can be obtained from the cost of production plus the expected profit. The data used are primary data and secondary data. Primary data was obtained by researchers from direct interviews with UMKM owners. Secondary data was obtained from reports on the production costs of UMKM Camilan Kampungku. The results of the study stated that the calculation of the cost of production produces a difference that affects the selling price.